Instant in-situ Tissue Repair by Biodegradable PLA/Gelatin Nanofibrous Membrane Using a 3D Printed Handheld Electrospinning Device - Chen, Hongrang; Zhang, Haitao; Shen, Yun; Dai, Xingliang; Wang, Xuanzhi; Deng, Kunxue; Long, Xiaoyan; Liu, Libiao; Zhang, Xinzhi; Li, Yongsheng; Xu, Tao (Frontiers in Bioengineering and Biotechnology, 2021)
Background This study aims to design a 3D printed handheld electrospinning device and evaluate its effect on the rapid repair of mouse skin wounds. Methods Device was developed by Solidworks and printed by Object 350 photosensitive resin printer. The Polylactic acid (PLA)/gelatin blend was used as the raw material to fabricate in-situ degradable nanofiber scaffolds. Scanning electron microscopy (SEM), fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and water vapour permeability test were used to evaluate the material properties of the scaffolds; Cytotoxicity test were performed to evaluate material/residual solvent toxicity, in-situ tissue repair experiments in Balb/c mouse were performed. Results 3D printed handheld electrospinning device successfully fabricate PLA/gelatin nanofibrous membrane with uniformly layered nanofibers, and good biocompatibility. Animal experiments showed that the mice in the experimental group had complete skin repair. Conclusions 3D printed handheld device can achieve in-situ repair of full-thickness defects in mouse skin.